LEGAL ANALYSIS OF TRAFFIC VIOLATIONS BY A DRIVER CAUSING DEATH IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 1785/PID.SUS/2025/PN MDN - Andri Gunawan Hasibuan; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the research results and concluded that the law enforcement procedures for traffic violations that cause death based on Medan District Court Decision Number 1785 / Pid.Sus / 2025 / PN Mdn include the stages of handling at the scene of the crime, arrest and detention, investigation, determination of suspects, submission of case files to the public prosecutor, prosecution in court, court decision. Criminal liability for traffic negligence that causes the loss of life of another person in Decision Number 1785 is in the form of imprisonment for 4 years and 2 months. The judge's consideration in the case of traffic negligence that causes the loss of life of another person in decision number 1785 is quite appropriate. However, the proof of the element "Due to negligence resulting in a traffic accident" only uses evidence of the defendant's statement, while other evidence is not explained.